2010 International Conference on Computational Intelligence and Software Engineering 2010
DOI: 10.1109/cise.2010.5677099
|View full text |Cite
|
Sign up to set email alerts
|

The Crossing Number of Cartesian Products of Stars with 5-Vertex Graphs

Abstract: Garey and Johxon have proved that the problem to determine the crossing number of graphs is NP-complete. Because of its difficulty, presently we only know the crossing number of some classes of special graphs. The crossing number of cartesian products of paths and cycles with 5-vertex graphs mostly are known, but only few cartesian products of 5-vertex graphs with star n K , 1 are known. In this paper, we extent those results,and determine the crossing numbers of cartesian products of two 5-vertex graphs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Tests with QuickCross have confirmed that it is possible to find drawings with the latter number of crossings, e.g. see Figure 31 in which drawings of G 5 3 ✷S 3 and G 5 4 ✷S 3 are drawn with four crossings, rather than the five suggested by [65]. • In 2016, Hsieh and Lin [74] claimed to have determined the crossing number of the join product of various path powers with discrete graphs and path graphs.…”
Section: A3 Incorrect Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Tests with QuickCross have confirmed that it is possible to find drawings with the latter number of crossings, e.g. see Figure 31 in which drawings of G 5 3 ✷S 3 and G 5 4 ✷S 3 are drawn with four crossings, rather than the five suggested by [65]. • In 2016, Hsieh and Lin [74] claimed to have determined the crossing number of the join product of various path powers with discrete graphs and path graphs.…”
Section: A3 Incorrect Resultsmentioning
confidence: 98%
“…• In 2011, He [65] considered the crossing number of G 5 3 ✷S n and G 5 4 ✷S n and claimed that both were equal to 4 n + n 2 for n ≥ 1. However, these results are contradicted by [17] and Klešč (2009) [95] respectively, who showed that each has crossing number equal to 3 n 2 n−1 2…”
Section: A3 Incorrect Resultsmentioning
confidence: 99%
“…For six remaining graphs G i on five vertices, the problem of estimating cr(G i S n ) is still open, even though some incorrect result were published. For example, in [8] the incorrect proof states that for the tree T on five vertices with one vertex of degree two and one vertex of degree three, the crossing number of T S n is 4⌊ n 2 ⌋⌊ n−1 2 ⌋ + ⌊ n 2 ⌋. This contradicts Corollary 9.…”
Section: Commentsmentioning
confidence: 98%
“…The Crossing number of G Â P n is known for all graphs G of order at most five, see [11,14,15,17] and for several graphs G of order six is given in [4,19]. The crossing number of G Â C n is established for all graphs G with at most four vertices in [1,10] and for some graphs on five or six vertices [6,14,18]. The crossing number of G Â S n for all graphs G of orders three or four is determined in [11,14,15] and for some graphs of order five is given in [10,16,17,20].…”
Section: Introductionmentioning
confidence: 99%
“…The crossing number of G Â C n is established for all graphs G with at most four vertices in [1,10] and for some graphs on five or six vertices [6,14,18]. The crossing number of G Â S n for all graphs G of orders three or four is determined in [11,14,15] and for some graphs of order five is given in [10,16,17,20]. Jha and Devishetty have analyzed the upper bounds for crossing number of Kronecker product of two cycles in [12].…”
Section: Introductionmentioning
confidence: 99%